Addicted to rehab : race, gender, and drugs in the era of mass incarceration - McKim, Allison (New Brunswick : Rutgers University Press, 2017)
Sociologist Allison McKim gives an in-depth and innovative ethnographic account of two women's rehab programs, one located in the criminal justice system and one located in the private healthcare system--two very different ways of defining and treating addiction. Her study ultimately reveals a two-tiered system, bifurcated by race and class. Â Â
Series Page; Title Page; Copyright Page; Dedication; Contents; Introduction: Rehab Is the New Black; Chapter 1: Intake. Pathways to Treatment; Chapter 2: Women's Treatment Services. Addicted to Punishment; Chapter 3: Women's Treatment Services. Habilitating Broken Women; Chapter 4: Gladstone Lodge. Haven for the Chemically Dependent; Chapter 5: Gladstone Lodge. Learning to Live Sober; Conclusion. Governing through Addiction; Methodological Appendix; Acknowledgments; Notes; Bibliography; Index; About the Author; Read More in the Series
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 14, 2017).
eBooks on EBSCOhost
Keywords: Drug addiction -- Treatment -- United States; Drug addicts -- Rehabilitation -- United States; Women's rights; Substance-Related Disorders -- rehabilitation; Social Marginalization; Institutionalization; Women's Rights; Minority Health; Rehabilitation Centers -- ethics; United States; Toxicomanie -- Traitement -- États-Unis.; Toxicomanes -- Réadaptation -- États-Unis.; Femmes -- Droits; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Social Classes; Drug addiction -- Treatment; Drug addicts -- Rehabilitation; United States; Drogentherapie; Haft; Weibliche Drogenabhängige; USA